The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1364/oe.463522
|View full text |Cite
|
Sign up to set email alerts
|

Metal-insulator-metal strip spectroscopic infrared photothermal absorber based on uniaxially oriented plasmonic lanthanum hexaboride films

Abstract: We report the fabrication of a mid-infrared device using LaB6 – Al2O3 – LaB6 trilayers, with an array of LaB6 strips as the top layer. Uniaxially oriented lanthanum hexaboride (LaB6) films self-organized in a (100) orientation were adopted together with a lithographic process using laser direct writing followed by reactive ion etching. The fabricated infrared absorbers based on our electromagnetic design exhibited excellent resonant absorption and flexible tunability by changing the periodicity and width of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Similar reports showed the temperature-dependent field emission (FE) in LaB 6 nanowires (70–130 nm thick and 10 μm length), and the emission current of aligned LaB 6 nanowire arrays increased by ∼45 times (to 9.05 mA/cm 2 ) at 2.20 V/μm when the temperature increased from RT to 723 K. The authors of this study suggested that such good FE performance LaB 6 nanowires have the potential for thermionic emission, field-induced emission valuable for TEM, SEM, and flat panel displays, as well as direct thermal to electrical converters . Besides being a field emitter, LaB 6 is also a plasmonic material with absorption in the range of 600 to 2000 nm; Tran et al reported a photothermal absorber using LaB 6 –Al 2 O 3 –LaB 6 trilayers . The ⟨100⟩ orientation-grown LaB 6 films were developed by a lithographic process using laser direct writing and reactive ion etching.…”
Section: Metal Borides For Heterogeneous Catalysissupporting
confidence: 81%
See 2 more Smart Citations
“…Similar reports showed the temperature-dependent field emission (FE) in LaB 6 nanowires (70–130 nm thick and 10 μm length), and the emission current of aligned LaB 6 nanowire arrays increased by ∼45 times (to 9.05 mA/cm 2 ) at 2.20 V/μm when the temperature increased from RT to 723 K. The authors of this study suggested that such good FE performance LaB 6 nanowires have the potential for thermionic emission, field-induced emission valuable for TEM, SEM, and flat panel displays, as well as direct thermal to electrical converters . Besides being a field emitter, LaB 6 is also a plasmonic material with absorption in the range of 600 to 2000 nm; Tran et al reported a photothermal absorber using LaB 6 –Al 2 O 3 –LaB 6 trilayers . The ⟨100⟩ orientation-grown LaB 6 films were developed by a lithographic process using laser direct writing and reactive ion etching.…”
Section: Metal Borides For Heterogeneous Catalysissupporting
confidence: 81%
“…164 Besides being a field emitter, LaB 6 is also a plasmonic material with absorption in the range of 600 to 2000 nm; Tran et al reported a photothermal absorber using LaB 6 −Al 2 O 3 −LaB 6 trilayers. 184 The ⟨100⟩ orientation-grown LaB 6 films were developed by a lithographic process using laser direct writing and reactive ion etching. The sputtered films showed low surface roughness of ∼2.5 nm, and their optical performance in the near-infrared (NIR) regions showed better performance than those of molybdenum, tungsten, and titanium nitride.…”
Section: Applications In Electrocatalysismentioning
confidence: 99%
See 1 more Smart Citation